The Zero Effect: An Eye-Tracking Study of Affect and Motivation in Risky Choices - Jonas Ludwig; Alexander Jaudas; Anja Achtziger (Journal of Behavioral Decision Making, 2024)
Decision makers often prefer safe wins over risky gambles, even if the latter promise higher payoffs than the former. One mechanism that explains this choice pattern is the certainty effect, whereby probabilities of 0 and 1 are interpreted accurately but intermediate probabilities are distorted by diminishing sensitivity. We tested an alternative explanation that was recently proposed, the idea that people would be motivated by avoiding zero outcomes rather than being attracted to sure gains. This zero-outcome aversion in gain-domain choices was called the zero effect. By analogy, we proposed that decision makers would approach zero outcomes in the loss domain. Two eye-tracking experiments investigated visual attention as a key component of the zero effect in the gain domain (Experiment 1) and the loss domain (Experiment 2). Choices were consistent with the zero effect. In the gain domain, gambles were chosen less frequently if they included a zero outcome. In contrast, zero-outcome gambles were chosen more frequently in the loss domain. Eye movements and pupillometry indicated that zero outcomes in both domains (a) were less frequently fixated than other outcomes and (b) were associated with increased arousal. We concluded that domain-specific affective responses to zero outcomes aligned with approach/avoidance motivation. These distinct motivations in turn biased information search and choice behavior.
Keywords: 650; certainty effect; decisions under risk; eye-tracking; motivation; pupillometry; zero effect